Future Directions in Oncofertility and Fertility Preservation: A Report from the 2011 Oncofertility Consortium Conference - Waimey, Kate E. (Mary Ann Liebert, Inc., 2013)
Fertility impairment and loss due to cancer or its treatment is a significant survivorship consideration for many pediatric, adolescent, and young adult cancer survivors. Chemotherapeutics, radiation, and surgery can impact the future fertility of men, women, and children with cancer. The field of oncofertility, founded to ensure the reproductive future of cancer survivors, gained momentum with 5 years of funding through a 2007 National Institutes of Health Roadmap Grant for Biomedical Research. This report from working group meetings at the fifth annual Oncofertility Consortium Conference speaks to the present state of oncofertility research and clinical care, existing gaps, and future directions for the field. This summary from conference participants and leaders in the field addresses the science, clinical specialties, and academic scholarship that can guide the field as the Roadmap Grant funding comes to a close.